2024
DOI: 10.2196/55627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ChatGPT-4’s Diagnostic Accuracy: Impact of Visual Data Integration

Takanobu Hirosawa,
Yukinori Harada,
Kazuki Tokumasu
et al.

Abstract: Background In the evolving field of health care, multimodal generative artificial intelligence (AI) systems, such as ChatGPT-4 with vision (ChatGPT-4V), represent a significant advancement, as they integrate visual data with text data. This integration has the potential to revolutionize clinical diagnostics by offering more comprehensive analysis capabilities. However, the impact on diagnostic accuracy of using image data to augment ChatGPT-4 remains unclear. Objec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Despite this, we found that DxGPT demonstrated minimal response inconsistencies among replicates, highlighting its robustness. As LLMs continue to evolve and surpass their previous capabilities 2, 10,13,14 , and with the potential for specialized medical training and refinement 15 , we anticipate future models will further improve diagnostic accuracy, potentially exceeding the performance of clinical experts. However, regardless of the specific performance metrics of any LLM-based tool 16 , correct tool usage remains crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, we found that DxGPT demonstrated minimal response inconsistencies among replicates, highlighting its robustness. As LLMs continue to evolve and surpass their previous capabilities 2, 10,13,14 , and with the potential for specialized medical training and refinement 15 , we anticipate future models will further improve diagnostic accuracy, potentially exceeding the performance of clinical experts. However, regardless of the specific performance metrics of any LLM-based tool 16 , correct tool usage remains crucial.…”
Section: Discussionmentioning
confidence: 99%